Homogenitas Cuitan Tabu Generasi Y dan Z dalam Komunitas Ngeluh Safe Space di Aplikasi X - Dyah Nur Fadillah; Chattri Sigit Widyasuti (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
The use of language is considered one of the best means of communication to demonstrate interaction between social media users. One example is the interaction between Generations Y and Z in tweets on social media X. The large number of tweets uploaded has given rise to a linguistic phenomenon that can be studied, namely taboo language. This study focuses on taboo language that uses certain words or phrases in posts on social media X. The research was conducted to increase knowledge regarding the types, functions, and causes of the prevalence of taboo language among Generations Y and Z. The research method used was a descriptive qualitative method. The results of the study found taboo language among Generations Y and Z in the Ngeluh Safe Space community on the X application, covering 9 types of taboo language categories, 3 functions of taboo language, and 4 causes of taboo language usage.